TERAPI MESENCHYMAL STEM CELL SEBAGAI MODALITAS TATALAKSANA OSTEOARTRITIS - Theodorus, Emeraldha; Cinthya D Valentina, Debby; Agverianti, Theodora; Kusumaningrum Samosir, Renti (Essence of Scientific Medical Journal; Vol 19 No 2 (2021): Volume 19 No. 2 (Juli - Desember 2021) Essential: Essence of Scientific Medical Journal, 2022)
ABSTRACT MESENCHYMAL STEM CELL THERAPY AS OSTEOARTHRITIS TREATMENT MODALITY Introduction: Osteoarthritis (OA) is a degenerative and progressive disease with articular cartilage degradation, osteophyte formation, subcondral bone damage, and inflammation of the synovial membrane. The incidence of joint disease aged over 15 years in Indonesia as much as 15%, with 60% is OA in the knee. Recent research mentions the potential for mesechymal stem cell (MSC) as OA treatment. Discussion: The pathogenesis of OA involves activation of the immune system which causes a decrease in cartilage synthesis and cartilage damage. The immune system also triggers the activation of c-Jun NH 2-terminal Kinase (JNK) signaling pathway which causes cartilage degeneration. OA treatment has evolved into intra-articular therapy, one of which is mesenchymal stem cell (MSC). The mechanism of MSC in OA therapy is to stimulate type two collagen for cartilage regeneration, accelerate cartilage differentiation, and have anti-inflammatory effects. The use of MSC by autotransplantation can be taken through adipose tissue liposuction and bone marrow aspiration. The best use of allotransplantation MSC comes from Wharthon’s Jelly cells from human umbilical cord tissue (HUCT). Conclusion: Potency of mesechymal stem in cell cartilage’s tissue regeneration process and anti-inflammatory after oxidative stress exposure could be developed as a novel therapy modality to prevent worsening of the disease of patients with OA. Keywords: Osteoarthritis, Stem cell, Therapy